PENGARUH E-COMMERCE, SELF EFFICACY DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA PENGAMBILAN KEPUTUSAN DALAM BERWIRAUSAHA - Ayu Handayani Batubara; Isma Coryanata (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to evaluate three factors: the effect of e-commerce, self-efficacy, and accounting information systems on the decision to pursue entrepreneurship. This research uses an associative quantitative approach. The population in this study were active students of the accounting study program at the Faculty of Economics and Business, Bengkulu University. This research uses a survey method by distributing questionnaires. Using purposive sampling technique, this study involved active students majoring in accounting semesters 5 and 7 who took accounting information systems and entrepreneurship classes. Based on statistical tests conducted, the results showed that e-commerce and self-efficacy affect student entrepreneurship decisions, while accounting information systems have no effect on student entrepreneurship decisions. This research is expected to help students in making entrepreneurial decisions. In this way, they continue to develop their personal skills and accounting knowledge until they become successful entrepreneurs.